The Influence of Social Media Marketing and the Ease of Use of Mobile Banking on Customer Loyalty with Customer Satisfaction as a Mediator in Mobile Banking Services “Digi by Bank BJB” - Alysha Prameswari Nurmalitasari; Aang Curatman; Siska Ernawati Fatimah (International Journal Labs, 2026)
Many factors can affect customer loyalty, one of which is social media marketing. In addition to social media marketing, the ease of use of mobile banking can also affect customer loyalty. This study includes customer satisfaction as a mediating variable. The approach used in this study is quantitative. This is explanatory research. The population comprises 20,028 customers of Bank BJB who use